2007
DOI: 10.1093/ps/86.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Feed Restriction on Metabolic Programming and Compensatory Growth in Broiler Chickens

Abstract: The effect of early feed restriction on metabolic programming and compensatory growth was studied in broiler chickens. A total of 480 female 1-d-old broiler birds (Aconred) were randomly allocated to ad libitum and feed-restricted groups, each of which was replicated 6 times with 40 birds per replicate. Broilers were provided commercial diets. Feed-restricted broilers were deprived of feed for 4 h per day from 1 to 21 d of age. Effects of treatments were determined at 21 and 63 d of age. In feed-restricted bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
91
3
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 28 publications
12
91
3
14
Order By: Relevance
“…However, in this study the feed conversion of batch showed significant difference (p > 0.05) among treatments evaluated 28 to 49 days. Zhan, Wang, Ren, Zhao, Li & Tan, (2007), also showed no difference in relation to the feed conversion, analyzing the effect of early food restriction in metabolic programming and compensatory growth in broiler.…”
Section: Discussionmentioning
confidence: 96%
“…However, in this study the feed conversion of batch showed significant difference (p > 0.05) among treatments evaluated 28 to 49 days. Zhan, Wang, Ren, Zhao, Li & Tan, (2007), also showed no difference in relation to the feed conversion, analyzing the effect of early food restriction in metabolic programming and compensatory growth in broiler.…”
Section: Discussionmentioning
confidence: 96%
“…Feed restriction is a management strategy, which is applied in the poultry industry in order to reduce the feed intake, to limit the early growth, to decrease the incidence of infectious, metabolic and skeletal disorders and to improve the nutrient utilization via compensatory growth (Zulkifli et al, 1993;Zhan et al, 2007;Thompson et al, 2008;Benyi et al, 2010). In the present study, the reduction in body weight as well as the change of feed conversion ratio in experimental groups where feed restriction was applied, is in agreement with the results of the study of Lee & Leeson (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Feed restriction is applied in broiler chicks in order to take advantage of the growth compensation of birds and to reduce the feed conversion ratio. The growth compensation of birds defines the increased growth rate, when growth has been retarded by nutritional restriction and followed by ad libitum feeding (Shariatmadari & Torshizi, 2004;Zhan et al, 2007). In the beginning, feed restriction reduces the body weight, as a result of reduced feed consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations